The Green Economy Concept: A Guide for Future Economic Policy, Research, and Activity - Triandini, Noer Aida; Azarina, Puan; Satibi, Iswanda F. (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2025)
Short-term economic interest mostly neglects environmental concerns, resulting in continuous harmful impacts, including climate change. In response, the concept of green economy, which balances these conflicting interests, has attracted increasingly significant research attention. However, the green economy concept remains biased and vague. This study offers a novel contribution by systematically mapping the post-2016 evolution of the green economy concept, utilizing descriptive network analysis on a dataset of 11,301 Scopus-indexed articles to resolve prevailing definitional fragmentation. The study finds three main elements in the definitions offered: economic, environmental, and social , and highlights the multifaceted nature of trade-offs or synergies among these clusters. Consequently, the study defines the green economy concept as an economic philosophy, idea, and activity based on the principles of preserving the environment, enhancing public welfare, and maintaining social equity within and among generations. Theoretically, this consolidates the fragmented literature; practically, it provides a standardized framework for policymakers to design consistent green economy indicators and tracking mechanisms for future economic activity.